Doormatobezoar: first case report of a bezoar formed by doormat ingestion - Anand, Madhur; Topno, Noor; Lynrah, Kyrshanlang G.; Aggarwal, Swati (International Surgery Journal, 2023)
Bezoars are retained concretions of undigested foreign material that accumulate and coalesce within the gastrointestinal tract, most commonly in the stomach. A 12 years old male child presented to us with complaints of pain upper abdomen on and off for 2 months. He had a habit of biting and chewing doormat at home for several months. Physical examination revealed mild epigastric tenderness. Upper GI endoscopy revealed a mass of fibres in the stomach which was tightly organised and too large to safely remove endoscopically in toto. Hence patient was taken up for surgery and a mass of around 9×6 cm in size and oval in shape was removed from stomach. Postoperative recovery was uneventful. Doormatobezoars are rare cause of pain abdomen which can be treated safely and effectively surgically.